The Effect of Capital Account Liberalization on Income Inequality, focusing on South Asia - Hossain, Ridwan Mosharraf; Amin, Sakib Bin (International Journal of Economics and Financial Issues, 2022)
As a result of globalisation, countries across the world have opened their capital accounts, affecting economic growth, bargaining power of labor, and income inequality. A disproportionately large number of studies on capital account liberalization has focused on OECD and developed countries, leaving gaps in the literature for developing countries. To address this research gap, this paper focuses on the effect of capital account liberalization on changes in income inequality in South Asian countries, specifically Bangladesh, India, and Pakistan. Following Furceri and Lougani (2018), Li and Su (2020), and Quinn-Toyoda (2008), we examine the relationship between capital account liberalization and Gini coefficient as a measure of income inequality. Our findings reveal a small, positive, but statistically insignificant relationship between capital account liberalization and changes in income inequality for 149 countries, including South Asian countries of interest. The results from this study are inconclusive in determining if capital account liberalization exacerbates or reduces income inequality in the South Asian region.